Electoral Donations as Legal Bribes: Evidence from a Survey of Private Corporations in Colombia - Evertsson, Nubia (International Journal of Criminology and Sociology, 2012)
In this article I study why companies give electoral donations to support political leaders. I collected and used a unique data set on electoral financing at the corporate level in Colombia. The data show that firms consider electoral contributions to be ‘legal bribes’. Consistent with the theory of bribery, these donations are made because of the low quality of election regulation, the high expectation of reciprocity, and the pre-existing relationships with incumbents. These features suggest ‘legal neutralization’: donors can break the law without committing crime.